Der grüne Kakadu Historisch-kritische Ausgabe - Schnitzler, Arthur (Werke in historisch-kritischen Ausgaben, 2020)
In The Green Cockatoo, a one-act play from 1898, Arthur Schnitzler thematizes the indistinguishability of fiction and reality. The historical-critical edition reconstructs the history of the play and its publication, presents archival materials, and provides a print text and commentary. Moreover, it documents the censorship of the premiere at the Burgtheater in Vienna in 1899.